"Here's Where I Belong" Still, play adaptation of 'East of Eden - Friedman-Abeles Photos:::Creator::::::::::::
Adam Trask (Paul Rogers) and Cathy/Kate Ames (Nancy Wickwire). This play is an adaptation of John Steinbeck's 'East of Eden.' It ran for twenty previews and one night at the Billy Rose Theatre in New York. RESTRICTED USE Digital copy only. No hard copy.